Ambang Rasa Manis dan Kadar Glukosa Darah Puasa Pada Remaja di Surabaya Indonesia: Sweet Threshold and Fasting Blood Glucose Levels in Adolescents at Surabaya Indonesia - Rosalinda, Silvia; Farapti, Farapti; Sari, Afifah Nurma; Shanthi, Dhandapani (Amerta Nutrition, 2024)
Background: Diabetes mellitus (DM) is a degenerative disease characterized by elevated blood glucose levels (hyperglycemia). Based on Riskesdas 2018, the prevalence of diabetes mellitus diagnosed by doctors among the Indonesian population aged 15-24 years was 0.1%. The increase in blood glucose levels can be caused by high sugar consumption triggered by a high sweet taste threshold. Objectives: This study was conducted to investigate a relationship between the sweet threshold and fasting blood glucose levels in adolescents at Surabaya Indonesia. Methods: This cross-sectional study included  97 individuals selected through simple random sampling. The sweet taste threshold was carried out using three-alternative forced-choice (3-AFC) method. The sweet threshold was categorized as high if the sample could only answer <4 questions, while the normal category was defined as those who could answer >4 questions. Blood glucose measurements were performed by medical personnel using a glucometer, with a fasting blood glucose level of >100mg/dL considered high. Analysis was carried out using the Chi Square statistical test. Results: The results indicated that 12.4% of the respondents had a high sweet taste threshold, while 10.3% of the respondents had high fasting blood sugar levels. The results showed that there was no relationship between the sweet taste threshold and fasting blood glucose levels (p-value = 0.210). Conclusions: There is no relationship between the sweet taste threshold and fasting blood sugar levels in adolescents at Pondok Pesantren Subulussalam Surabaya. Respondents with high GDP levels should undergo further examination to facilitate early intervention and promote healthier lifestyles. Keywords: Taste Threshold, Diabetes Mellitus, Fasting Blood Glucose Level, Adolescent